أثر كل من الطريقتين القياسية والاستقرائية على التحصيل النحوي لدى طلاب الجامعة الإسلامية الحكومية شريف هداية الله بونتيانك أندونيسيا - Tabrani Solahudin (Kulliyah of Education, International Islamic University Malaysia, 1998)
The aim of this study is to identify the effectiveness of the deductive and inductive methods applied in teaching Arabic grammar based on test performance by First Year · Students of Arabic for Non-Arabic Speaker Students at the Arabic Department of the Faculty of Education in lAIN-Syarif Hidayatullah, Potianak, Indonesia. The selected areas on the Arabic grammar that have been taught and evaluated are : A 1-mubtada' wa al-khabar (al-mufrad, wa al-juml.ah, wa shibhul jumlah} "subject and predicate" (singular predicate, sentence predicate, phrase), wa khabar a!-mubtada' (ta'khirohu, wa taqdimuhu} "predicate of subject" (normal predicate, inverted predicate), wa al-fa 'ii (wa wujub ta 'nith al-ft 'ii ma 'ahu) "subject or doer and how to make feminine verb with it", wa al-maf'ul bih (alzahir, wa al tjamir, wa taqdimuhu) "object" (direct object, pronoun object, inverted object). This study compares the effectiveness of the two methods ( deductive and inductive) used on the students' ability to master the several rules of Arabic grammar. The study employed the experimental method. The sample for the study consisted of sixty students (thirty male and thirty female students) who were divided into two groups : deductive method and inductive method. Each group consisted of thirty students (fifteen male and fifteen female). The researcher used the t-test to answer the research questions and to examine the hypotheses The study found the following: 1.The Pre-test showed the students were weak in Arabic grammar. 2.The Post-test indicated an increase in students' achievement in learning the Arabic grammar after they have been taught by the deductive method. 3.There exists a significant difference between the two methods ( deductive and inductive) in students' achievements in learning several topics in Arabic grammar. 4.Tue deductive method is more effective than the inductive method.